2017
DOI: 10.1108/shr-07-2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

Thomson Reuters innovation case study

Abstract: Purpose The purpose of this case study is to demonstrate how you can generate employee enthusiasm through creative thinking and a campaign that drives engagement from the bottom up. Design/methodology/approach Creative solutions, engagement through early careers network, inclusion for all and democratizing the process. Findings Employees want to be engaged and feel like a part of the larger organization. If given the right opportunity, they will rise to the challenge and create a new momentum to drive inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Xerri and Brunetto (2013) applied social exchange theory and argued that staff who are committed will be more likely to be innovative. At Thomson Reuters Corporation, employees are given good opportunities and are committed to the organization; they, therefore, will have the momentum to innovate (Silverman, 2017). Research results on employee commitment within a large technology company carried out in Vietnam by Powell and Le (2016) showed that affective commitment predicts EI.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Xerri and Brunetto (2013) applied social exchange theory and argued that staff who are committed will be more likely to be innovative. At Thomson Reuters Corporation, employees are given good opportunities and are committed to the organization; they, therefore, will have the momentum to innovate (Silverman, 2017). Research results on employee commitment within a large technology company carried out in Vietnam by Powell and Le (2016) showed that affective commitment predicts EI.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Similarly, Silverman (2017) states that employees who have adequate opportunities are Researchers have also highlighted potentially unfavourable consequences of organisational commitment that may hamper innovativeness in employees. It is argued that committed employees display deep apprehension for the welfare of others which supersedes their personal concerns.…”
Section: Organisational Commitmentmentioning
confidence: 99%